The Well-Being of Russian Regions under Threat: Economic and Social Impact Assessment of COVID-19 - Ekaterina V. LISOVA; Igor V. PETROV; Tatyana V. KORYAKINA; Victoria I. KALOMBO MULAMBA andEvgeniya K. KARPUNINA (Communications of International Proceedings, 2020)
The purpose of the study is to reveal the nature and consequences of the economic and social impact of the coronavirus pandemic on the dynamics of Russian regions development. The authors described the economic consequences of the pandemic for the regions of the Russian Federation by analyzing key indicators of their socio-economic development. The top 10 regions that are most stable to the impact of the pandemic and the top 10 outsider regions for each analyzed indicator by economic sector are presented. The focus is on studying the structure of regional economies, identifying the most resistant to a decline in economic activity during the pandemic, and determining regions that have internal potential to deal with risks. The authors analyzed the most effective state support measures implemented by European countries and the United States in comparison with those proposed by the Russian Government.
Keywords: region; COVID-19 pandemic; Russia; economic damage; social consequences; economic barrier